2016
DOI: 10.1038/bmt.2016.293
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics and outcome of allogeneic transplantation in first remission of acute myeloid leukemia: the French pediatric experience

Abstract: We analyzed the impact of cytogenetics on 193 children enrolled in two successive French trials (LAME89/91 and ELAM02), who received hematopoietic stem cell transplantation during CR1. Detailed karyotype was available for 66/74 (89%) in LAME89/91 and 118/119 (99%) in ELAM02. Several karyotype and transplant characteristics differed according to therapeutic protocol: unfavorable karyotypes were more frequent in ELAM02 (36% vs 18%), pretransplant chemotherapy included high-dose cytarabine in ELAM02 and not in LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In our study, c ytogenetics risk was strongly related to OS, EFS, NRM and GRFS in multivariable analysis. However, children had more often high-risk cytogenetics, but did not experience a higher incidence of relapse, and had a higher EFS, which was in concordance with the study of Alloin et al that found a significant survival improvement for children with unfavorable karyotype due to the decrease of relapse risk over time (Alloin et al 2017 ). Furthermore, through age groups, there are observable differences in mutated genes, somatic structural variants and DNA methylation patterns (Bolouri et al 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, c ytogenetics risk was strongly related to OS, EFS, NRM and GRFS in multivariable analysis. However, children had more often high-risk cytogenetics, but did not experience a higher incidence of relapse, and had a higher EFS, which was in concordance with the study of Alloin et al that found a significant survival improvement for children with unfavorable karyotype due to the decrease of relapse risk over time (Alloin et al 2017 ). Furthermore, through age groups, there are observable differences in mutated genes, somatic structural variants and DNA methylation patterns (Bolouri et al 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…Median (range) age at diagnosis was 14.5 years (11.1‐17.5). All patients had received first‐line treatment according to the ELAM02 protocol (Table 1): induction included cytarabine 1400 mg/m², mitoxantrone 60 mg/m², and at least one intrathecal injection of methotrexate, cytarabine, and hydrocortisone 1 . The eight patients had refractory disease after induction, with a median (range) residual blast count of 30% (2‐90).…”
Section: Methodsmentioning
confidence: 99%
“…Until 2018, first‐line therapy in France was applied according to the ELAM02 protocol: patients received cytarabine and mitoxantrone for induction, and high‐dose cytarabine and amsacrine as consolidation. However, under this regimen, 10% of patients did not respond and were considered refractory 1 . There are currently no recommendations concerning second‐line treatment, and few therapeutic options are available.…”
Section: Introductionmentioning
confidence: 99%
“…We retrospectively analyzed CBF AML patients with targeted sequencing data from the French AML Intergroup central laboratory (Lille University Hospital) and the Munich Leukemia Laboratory (MLL). The cohort included 142 adult patients from the French AML Intergroup CBF2006 trial 20 (ClinicalTrials.gov NCT00428558) and 73 children enrolled in the pediatric ELAM02 trial (NCT00149162), 21 whose mutational profiling was previously reported, 4 as well as 230 patients referred from different German centers to the MLL, including 124 of 139 previously reported t(8;21) cases with adequate material 8 and 106 unreported inv(16)/t(16;16) cases (supplemental Figure 1, available on the Blood Web site). French patients were diagnosed between October 2005 and November 2011, and German patients were diagnosed between August 2005 and January 2015.…”
Section: Patients and Treatmentsmentioning
confidence: 99%